Analysis of the integration of human papillomaviruses in head and neck tumours in relation to patients' prognosis - Vojtechova, Zuzana; Sabol, Ivan; Salakova, Martina; Turek, Lubomir; Grega, Marek; Smahelova, Jana; Vencalek, Ondrej; Lukesova, Eva; Klozar, Jan; Tachezy, Ruth (International journal of cancer, 2016)
Integration, which leads to the disruption of the circular HPV genome, is considered as a critical, albeit not obligatory, step in carcinogenic progression. Although cervical carcinomas with extrachromosomal HPV plasmid genomes have been described, the virus is integrated in 70% of HPV16-positive cervical tumours. Limited information is available about HPV integration in head and neck tumours (HNC). In this study, we have characterised the physical status of HPV in a set of tonsillar tumour samples using different methods--the mapping of E2 integration breakpoint at the mRNA level, the 3' RACE based Amplification of Papillomavirus Oncogene Transcripts (APOT) assay and Southern blot. Furthermore, the impact of HPV integration on patients' prognosis has been evaluated in a larger set of 186 patients with head and neck cancer. Based on the analysis of E2 mRNA, HPV was integrated in the host genome in 43% of the HPV-positive samples. Extrachromosomal or mixed form was present in 57%. In fresh frozen samples, the APOT and E2 mapping results were in agreement. The results were confirmed using Southern blotting. Furthermore, the type and exact site of integration were determined. The survival analysis of 186 patients revealed HPV positivity, tumour size and lymph node positivity as factors that influence disease specific survival. However, no statistically significant difference was found in disease specific survival between patients with HPV-positive integrated vs. extrachromosomal/mixed forms of the virus.
Keywords: proporcionální rizikové modely; Squamous Cell Carcinoma of Head and Neck; Tonsillar Neoplasms; survival; Male; dlaždicobuněčné karcinomy hlavy a krku; head and neck tumours; tonzilární nádory; infekce papilomavirem; Papillomavirus Infections; prognóza; Southernův blotting; Proportional Hazards Models; nádory hlavy a krku; Head and Neck Neoplasms; mužské pohlaví; Virus Integration; prognosis; lidé; ženské pohlaví; Humans; integration; integrace viru; Prognosis; HPV; Blotting, Southern; spinocelulární karcinom; Female; Carcinoma, Squamous Cell